The efficiency of the cognitive representation of in formation among the students of Kirkuk university (Journal of Humanities and Social Sciences Research, 2023)
The current research aims to know efficiency levels of knowledge representation of information among Kirkuk university students  and The statistically significant difference of the cognitive representation of information regarding gender(female ,males), specialization(scientific ,human ) and stage (first ,fourth). for the interactions between the cognitive efficiency variable of information  and the variables (gender, specialization , stage). In order to achieve the objectives of the research ,the researcher adoption scale (The competency of the cognitive representation of the  teacher)consisting of (46)paragraphs ,and each paragraph(5) within it (applies to me completely , applies to  me often ,applies to me sometimes , applies to  me rarely,  never apples.